Larangan Perkawinan Sesuku pada Masyarakat Adat Kenegerian Logas Tanah Darat (Luhak Nan Sambilan) Riau - Egi Lumban Gaol; Erlina Erlina; Zulherman Idris; Heni Susanti; Yusril Sabri (Proceeding International Conference on Malay Identity, 2021)
Abstract: Along with the times, now the indigenous Mandailing people can be found in various regions throughout Indonesia. One of the areas where the Mandailing indigenous people can be found is in the Rokan Hulu Regency of Riau. The Mandailing indigenous people in the area live by customary values ??brought from their place of origin, including in the field of marriage. The author is interested in researching how traditional marriages are carried out in the Mandailing community, especially nasution in the current era of globalization. This research was conducted using empirical methods, using primary data, and inductively concluded. The results of the study show that in the development of people's lives, especially in the current era of globalization, some members of the community do not practice it due to economic factors that make it difficult to make honest money payments to women, there are changes in people's thinking that are influenced by modernization or also influenced by foreign cultures Keywords: prohibition; marriage; tribes. Abstrak: Perkawinan Sesuku merupakan perbuatan yang dilarang oleh adat istiadat yang berlaku Pada Masyarakat Adat Kenegerian Logas Tanah Darat (Luhak Nan Sambilan) Riau. Tetapi fenomena yang terjadi masih adanya masyarakat yang melangsungkan perkawinan Sesuku. Penelitian ini bertujuan untuk mengetahui penyebab larangan perkawinan sesuku dan peran ninik mamak dalam menangani permasalahan terjadinya perkawinan sesuku. Permasalahan penelitian ini tentang penyebab larangan perkawinan sesuku dan peran ninik mamak dalam menangani permasalahan terjadinya perkawinan sesuku di Kenegerian Logas Tanah Darat (Luhak Nan Sambilan) Riau. Metode penelitian ini adalah penelitian Observasi, dengan melakukan wawancara dan kuisioner terhadap objek penelitian. Hasil penelitian penyebab dilarangnya perkawinan sesuku adalah orang yang melakukan perkawinan sesuku sama saja dengan menikahi saudaranya sendiri, karena pada jaman nenek moyang dahulu mereka merupakan saudara sesusuan, menyempitkan pergaulan, melahirkan keturunan yang kurang berkualitas, serta pisikologis anak. Katakunci: larangan; perkawinan; sesuku